EFFECT OF ISOLATED PROBIOTIC LACTOBACILLUS PLANTARUM N24 ON GROWTH AND HAEMATOLOGICAL PERFORMANCES IN MALE ALBINO RATS - Fakorede, Christopher; Aforijiku, Samuel; Okere, Isaiah; Adediran, Arinola (Food and Feed Research, 2025)
Lactic Acid Bacteria (LAB) are known probiotic microorganisms whose presence in food such as yoghurt is immensely beneficial. We investigated the potential of Lactobacillus plantarum N24 on physical and haematological parameters in Wistar albino rats. Standard microbiological techniques were used to isolate LAB from raw cow milk. The LAB was screened for strain-level identification using 16S rRNA gene sequencing. Yoghurt was prepared with probiotics using L. plantarum N24. In vivo assessment of three Groups (G1-G3) of Wistar albino rats (n=9), G1: rats fed with animal feeds, G2: rats fed with animal feeds and prepared probiotic yoghurt, G3: rats fed with animal feeds and live probiotic commercial yoghurt) and were monitored for weight gain, certain haematological parameters and Lactobacilli count. Data were analysed using descriptive statistics and ANOVA at a p-value of 0.05. This study revealed appreciable weight gain from 11.00±1.00 g on day 7 to 40.00±1.15 g on day 28. A significant improvement in feed intake and feed efficiency ratio was observed in the animals in G2 compared to other groups. The PCV (%), WBC (x109/L), RBC (x106µl) and Lactobacilli count (x106 cfu/mL) were significantly better in G2 (49.7±2.4, 9.1±0.07, 8.71±0.20, 22.0±16.0) than in G1 (39.3±1.5, 7.67±0.19, 8.50±0.50, 0.46±0.04); and G3 (46.3±1.5, 7.30±0.33, 8.63±0.20, and 3.57±0.70, respectively) indicating the potential benefits of L. plantarumN24 as probiotics. L. plantarum N24 was a suitable probiotic candidate and could be used as a supplement to promote growth and increase or maintain the beneficial gut microflora.